SYSTEMATIC LITERATURE REVIEW: PERAN KOMUNIKASI INTERPERSONAL PELATIH DALAM PEMULIHAN MOTIVASI ATLET BASKET REMAJA PASCA CEDERA : Kajian Literature Review - Oktavia, Renita Enji; Pramana, Ida Bagus Gde Agung Yoga; Putra, I Gusti Agung Ananda; Srikandi, Melati Budi (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study is a literature review that aims to describe previous research as a source of academic literature and to identify patterns and trends in research themes. The review was conducted by examining a number of articles published between 2020 and 2025 using the Systematic Literature Review (SLR) method. The article selection process followed the PRISMA guidelines, and the data were subsequently analyzed using thematic analysis techniques. The findings indicate that out of 10 articles that passed the title and abstract screening stages, there is a relationship between communication patterns and interpersonal communication models applied by coaches and athletes in motivating basketball athletes during post-injury recovery. Theoretically, this study contributes to the development of DeVito’s interpersonal communication theory by demonstrating the relevance and application of the components of openness, empathy, support, positivity, and equality within the context of coach–athlete communication. The findings also show that interpersonal communication plays a role in building supportive relationships and serves as one aspect of coaching competence in motivating adolescent athletes to return to training after injury. Furthermore, this review identifies a research gap in interpersonal communication studies that integrate motivational psychology within the sports context, which may provide opportunities for future research. Keywords: Adolescent Basketball Athletes; Coaches; Coach–Athlete Communication; Interpersonal Communication; Post-Injury Motivational Psychology; Sports Communication;